Magnetron sputtering fabrication of α-Al2O3:Cr powders and their T thermoluminescence properties - Grigorjeva, Larisa; Zolotarjovs, Aleksejs; Millers, Donats; Smits, Krisjanis; Krug, Peter; Stollenwerk, Johannes; Osman, Alan; Tenostendarp, Thomas (Elsevier B.V., 2018)
For many years doped α-Al2O3 has attracted interest as a dosimeter for personal, environment monitoring and food control. The alumina single crystal growth is a difficult process; however, materials in form of powders, ceramics and coating are possible to obtain. In this study for the first time Cr doped α-Al2O3 powders were prepared by DC reactive magnetron sputtering followed by milling and oxidation. The morphology and phase analysis was performed; content of residual impurities was determined and thermostimulated glow curves were measured after different x-ray irradiation times (radiation doses). The prepared powder shows the dosimetry properties up to 20 kGy dose.
The authors gratefully acknowledge the financial support for this work from research grant ERA.NET RUS Plus Nr.609556.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; Magnetron sputtering; Chromium doped alumina; Thermostimulated luminescence